2006
DOI: 10.1093/brain/awl302
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic stimulation modulates cortical control of urinary bladder in Parkinson's disease

Abstract: Subthalamic nucleus deep brain stimulation (STN-DBS) is an effective therapy for off-period motor symptoms and dyskinesias in advanced Parkinson's disease. Clinical studies have shown that STN-DBS also ameliorates urinary bladder function in Parkinson's disease patients by delaying the first desire to void and increasing bladder capacity. This study aimed at investigating the effect of STN-DBS on the neural mechanisms underlying cerebral bladder control. Using PET to measure changes in regional cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 66 publications
6
73
0
6
Order By: Relevance
“…The location of peak activity in STN identified both in the current study and in Aron and Poldrack appeared to be somewhat medial to the MNI coordinates specified in previous studies (e.g., x=18, right STN, x=−16, left STN, Herzog et al, 2006). Thus, we overlay the BOLD activation for long>short SSRT on coronal and axial sections of a single-subject T1 structural image in order to better visualize the approximate locations of the STNs (Fig.…”
Section: Neural Activity Differentiating Individuals With Short and Lsupporting
confidence: 50%
“…The location of peak activity in STN identified both in the current study and in Aron and Poldrack appeared to be somewhat medial to the MNI coordinates specified in previous studies (e.g., x=18, right STN, x=−16, left STN, Herzog et al, 2006). Thus, we overlay the BOLD activation for long>short SSRT on coronal and axial sections of a single-subject T1 structural image in order to better visualize the approximate locations of the STNs (Fig.…”
Section: Neural Activity Differentiating Individuals With Short and Lsupporting
confidence: 50%
“…Other studies have shown that DBS of the STN positively influences urodynamic parameters during the storage phase (Finazzi-Agro et al, 2003). A recent study has demonstrated that this improvement of urinary bladder function is related to a decreased activation of the ACC and lateral PFC during bladder filling, which could be a consequence of the improvement of the continence (Herzog et al, 2006).…”
Section: Effect Of Dbs On Vegetative/autonomic Functionsmentioning
confidence: 94%
“…By using PET signals to observe regional cerebral blood flow (rCBF), bladder filling was found to significantly increase rCBF in the anterior cingulate gyrus and lateral frontal cortex. DBS improved the coordinated cortical control of pelvic floor muscle activity and eliminated supplemental motor and pre-motor activity resulting in the potential for improved UI in PD patients [15]. Further study of functional incontinence outcomes appears to be warranted by this initial innovative trial.…”
Section: Spinal and Deep Brain Stimulationmentioning
confidence: 98%